CHRONIC GENERALIZED PERIODONTITIS AND ITS SYSTEMIC COMPLICATIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Chronic generalized periodontitis is a prevalent inflammatory diseaseaffecting the supporting structures of the teeth, leading to progressive alveolar boneloss and eventual tooth loss. Beyond local oral manifestations, increasing evidenceindicates a strong association between periodontitis and systemic health conditions,including cardiovascular diseases, diabetes mellitus, respiratory disorders, and adversepregnancy outcomes. This article provides a comprehensive review of thepathophysiological mechanisms linking chronic generalized periodontitis withsystemic complications, highlighting the importance of early diagnosis, preventivestrategies, and interdisciplinary management to improve both oral and overall healthoutcomes.